Nutrition-sensitive Food Systems: Brief Perspectives - Bhattacharjee, Lalita; Seki, Richemont; Ashraf, Md Musharraf; Tontisirin, Kraisid (Bangladesh Journal of Nutrition, 2021)
Food systems – covering the ‘production to the plate’ chain – comprise food production, processing, marketing, utilization, and consumption. It facilitates peoples’ access to nutritious food in an adequate amount and variety necessary for maintaining a healthy life, irrespective of age, gender, culture, and social stratum. Food systems also address people’s access to information to facilitate their informed choice of food. To this end, food system elements and nutrition have linkages that offer opportunities for policy priorities, programs, and strategies. The trends in hunger and food insecurity, dietary consumption, and malnutrition appear to vary across the globe amidst the recurrent effects of global warming and socio-political crises which pose challenges for many developing countries to achieve the SDG 2.1 target. There is a need for strengthening the linkages between sustainable healthy diets for nutrition and between food systems and nutrition along with addressing the alterations in food systems amidst urbanization and diet changes. Policy actions should leverage nutrition sensitive agriculture and food systems with prospects for women, small holder farmers, and communities to improve diets and nutrition. Bangladesh J. Nutr. Vol. 34, December 2020, P: 25-39